Echocardiographic follow‐up after transcatheter aortic valve replacement. Issue 2 (3rd January 2017) - Sokalskis, Vladislavs; Muraru, Denisa; Fraccaro, Chiara; Napodano, Massimo; D'Onofrio, Augusto; Tarantini, Giuseppe; Badano, Luigi Paolo
Abstract : The use of transcatheter aortic valve replacement (TAVR) for high‐risk patients with aortic stenosis has rapidly increased during the past years. Accordingly, more and more patients are referred for a follow‐up echocardiographic study after TAVR. However, the echocardiographic evaluation of patients who underwent TAVR places specific demands on echocardiographers. Furthermore, TAVR may be associated with new types of complications, which are frequently unrecognized or underestimated due to lack of familiarity with the normal and pathological appearance of TAVR. Therefore, this review summarizes the echocardiographic parameters describing the structural and functional status of bioprostheses used in TAVR, procedures taking into account their peculiar hemodynamics. We also describe the strengths and the limitations of echocardiography and of other imaging modalities in detecting long‐term complications of TAVR (eg, infective endocarditis, thrombosis). The aim of this review was to serve as a guide for a structured echocardiographic follow‐up of TAVR patients, as well as for the echocardiographic diagnosis of the procedure‐associated complications.